Enrico Fermi a Firenze Le «Lezioni di Meccanica Razionale» al biennio propedeutico agli studi di Ingegneria: 1924-1926 - Casalbuoni, Roberto; Dominici, Daniele; Pelosi, Giuseppe (I libri de «Il Colle di Galileo», 2019)
Enrico Fermi, Nobel Prize for Physics in 1938, taught at the Royal University of Florence. Fermi's stay in Florence was short and only lasted two academic years (1924/25 and 1925/26); during those years, he taught "Mathematical Physics" and "Rational Mechanics" courses. This volume contributes to the reconstruction of this quite unknown period of Fermi's life, marked however by the publication of the Fermi statistics, a scientific breakthrough which would bring the Italian scientist to international celebrity thanks to its application in several fields of physics. This work is at the base, among other things, of semiconductor physics and therefore of modern electronics. The text also features Enrico Fermi's "Lessons of Rational Mechanics" to Science students and to students from the two-year preparatory course for Engineering studies during the aforementioned time span. The topics Enrico Fermi addressed in his lectures include kinematics and point dynamics, kinematics and statics of rigid systems and system statics in general. Lastly, the lessons contain 'Lagrangia''s equations and some elements of hydromechanics.